Metal-free nucleophilic trifluoromethylselenolation via an iodide-mediated umpolung reactivity of trifluoromethylselenotoluenesulfonate - Grollier, Kevin; Taponard, Alexis; De Zordo-Banliat, Arnaud; Magnier, Emmanuel; Billard, Thierry (Beilstein Journal of Organic Chemistry, 2020)
We report herein a practical method to generate CF3Se− (and RFSe−) anions from shelf-stable reagents under iodide activation. Metal-free nucleophilic trifluoromethylselenolations have been then performed with this in situ-generated anion. Perfluoroalkylselenolations have also been described.
Keywords: fluorine; nucleophilic substitution; perfluoroalkylselenolation; selenium; trifluoromethylselenolation